The complete plastid genome sequence of Abies koreana (Pinaceae: Abietoideae). (3rd July 2016) - Yi, Dong-Keun; Yang, Jong Cheol; So, Soonku; Joo, Minjung; Kim, Dong-Kap; Shin, Chang Ho; Lee, You-Mi; Choi, Kyung
Abstract: The nucleotide sequence of the chloroplast genome from Abies koreana is the first to have complete genome sequence from genus Abies of family Pinaceae. The circular double-stranded DNA, which consists of 121, 373 base pairs (bp), contains a pair of very short inverted repeat regions (IRa and IRb) of 264 bp each, which are separated by a small and large single-copy regions (SSC and LSC) of 54, 197 and 66, 648 bp, respectively. The genome contents of 114 genes (68 peptide-encoding genes, 35 tRNA genes, four rRNA genes, six open reading frames and one pseudogene) are similar to the chloroplast DNA of other species of Abietoideae. Loss of ndh genes was also identified in the genome of A. koreana like other genomes in the family Pinaceae. Thirteen genes contain one (11 genes) or two (rps12 and ycf3 genes) introns. In phylogenetic analysis, the tree confirms that Abies, Keteleeria and Cedrus are strongly supported as monophyletic. Other inverted repeat sequences located in 42-kb inversion points (1186 bp) include trn S- psa M- ycf 12- ψ trn G genes.